2017
DOI: 10.3329/imcjms.v10i2.31108
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Rapid stool antigen test for the diagnosis of Helicobacter pylori infection in patients with dyspepsia

Abstract: Background and objectives: Several diagnostic assays are used for the detection of Helicobacter pylori infection in suspected peptic ulcer cases. H. pylori stool antigen test is a non-invasive method for the detection of active infection. The present study has evaluated the efficacy of rapid stool antigen test to diagnose H. pylori infection in patients with dyspepsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…It was 14.2% in African rural children [28]. Positive H. pylori stool antigen means active infection or individual is harboring the organism whereas positive H. pylori IgG antibodies represent current or previous H. pylori infection [29]. In our study, the H. pylori infection rate by serum anti-H. pylori IgG antibodies was 64.9% while the H. pylori stool antigen positivity rate was 24.9%.…”
Section: Discussionmentioning
confidence: 50%
“…It was 14.2% in African rural children [28]. Positive H. pylori stool antigen means active infection or individual is harboring the organism whereas positive H. pylori IgG antibodies represent current or previous H. pylori infection [29]. In our study, the H. pylori infection rate by serum anti-H. pylori IgG antibodies was 64.9% while the H. pylori stool antigen positivity rate was 24.9%.…”
Section: Discussionmentioning
confidence: 50%
“…In our previous study, we found that 83.5% of dyspeptic cases were positive for H. pylori infection either by stool antigen or serum anti-H. pylori IgA [11]. In the present study, we attempted to find out the anti-CagA IgG status in dyspeptic patients.…”
Section: Discussionmentioning
confidence: 87%